Mixed 1D-2D quantum electron transport in percolating gold film - Beliayev, E.Yu.; Belevtsev, B.I.; Kolesnichenko, Yu.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The gold film (mean thickness ≈ 3.5 nm) was condensed in high vacuum at temperature 70 K on single-crystal sapphire substrate. The transport properties of the film at low temperature reveal simultaneously indications of 1D and 2D quantum interference effects of weak localization and electron–electron interaction. It is shown that this behavior is determined by inhomogeneous electron transport at the threshold of thickness-controlled metal–insulator transition.